2018
DOI: 10.1002/ehf2.12253
|View full text |Cite
|
Sign up to set email alerts
|

The effect of diuresis on extravascular lung water and pulmonary function in acute decompensated heart failure

Abstract: AimsThe effect of extravascular lung water (EVLW) and relationship to functional status as a result of acute decompensated heart failure (ADHF) are not well understood. We sought to quantify changes in clinical variables, EVLW, airway anatomy, spirometry, and diffusing capacity for carbon monoxide before and after treatment for ADHF.Methods and resultsFifteen patients were recruited within 24 h of hospital admission. Spirometry, diffusing capacity for carbon monoxide, and surrogates of EVLW by computed tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…It is possible that for some subjects, even though the fluid is removed from the intravascular compartment, only a small portion of the total fluid is removed from the interstitial compartment during dialysis. 11 Supporting evidence of this phenomenon was found in a hemodialysis study, where 31% of subjects following dialysis still had moderate to severe pulmonary congestion demonstrating that fluid removal is often not completely fulfilled. 8 It is also possible that individuals with mild pulmonary congestion may experience a more dramatic change in TFI.…”
Section: Discussionmentioning
confidence: 94%
“…It is possible that for some subjects, even though the fluid is removed from the intravascular compartment, only a small portion of the total fluid is removed from the interstitial compartment during dialysis. 11 Supporting evidence of this phenomenon was found in a hemodialysis study, where 31% of subjects following dialysis still had moderate to severe pulmonary congestion demonstrating that fluid removal is often not completely fulfilled. 8 It is also possible that individuals with mild pulmonary congestion may experience a more dramatic change in TFI.…”
Section: Discussionmentioning
confidence: 94%
“…The improvement of left ventricular heart function in the resveratrol-treated group is in-line with the decreased volume retention and with the decongestion of organs. It is known that extravascular fluid accumulation in the lungs is accompanied by the alteration of several spirometry measures, e.g., forced vital capacity (FVC) and inspiratory vital capacity (IVC) [ 53 , 54 ]. Moreover, Gehlback et al showed that, after heart transplantation, not only the ventilation volumes but the airflow velocity (FEV1) was also better [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, increased ultrafiltration volume was independently associated with higher FVC [7]. Similarly, Chase and colleagues demonstrated that increased extravascular lung water, impaired gas exchange and lung compliance was modifiable by enhanced fluid removal [8]. Similarly, Alves et al demonstrated that sessional ultrafiltration was associated with an acute increase in FEV1 and FVC [9].…”
Section: Discussionmentioning
confidence: 99%